Ответы и объяснения

2013-11-24T10:01:37+00:00
2. a) 2\sqrt{5}- \sqrt{45}  + \sqrt{80} =2 \sqrt{5} -3\sqrt{5} +4\sqrt{5} =3\sqrt{5}
б) ( \sqrt{a} + \sqrt{b}) ( \sqrt{a} - \sqrt{b}) -b=a-b-b=a-2b
5. ( \frac{ \sqrt{3} }{ \sqrt{3}-2 } - \frac{3}{\sqrt{3}+2} )( \sqrt{3}+9)= \frac{ \sqrt{3} ( \sqrt{3}+2) - 3( \sqrt{3}-2) }{( \sqrt{3}-2)( \sqrt{3}+2)} ( \sqrt{3}+9)= \frac{3+2 \sqrt{3}-3\sqrt{3}+6 }{3-4}( \sqrt{3}+9)= -(9- \sqrt{3} )( \sqrt{3}+9)=( \sqrt{3}-9)( \sqrt{3}+9)=3-81=-78


Сейчас дорисую ещё
спасибо тебе большое :))